45.9k views
3 votes
Find the solution of IVP for the differential equation (x+2)^2e^y when y(1) =0 y'= dy/dx=(x+2)^2.e^y; y(1)=0

User Svoychik
by
4.9k points

1 Answer

7 votes

Answer:

The solution is
y\:=-\ln(-(x^(3))/(3)-4x-2x^(2)+(22)/(3))

Explanation:

We need to find the solution of IVP for differential equation
(dy)/(dx)=(x+2)^(2)e^(y) when
y(1)=0


\mathrm{First\:order\:separable\:Ordinary\:Differential\:Equation}


\mathrm{A\:first\:order\:separable\:ODE\:has\:the\:form\:of}\:N\left(y\right)\cdot y'=M\left(x\right)


\mathrm{Rewrite\:in\:the\:form\:of\:a\:first\:order\:separable\:ODE}


(1)/(e^y)y'\:=\left(x+2\right)^2


N\left(y\right)\cdot y'\:=M\left(x\right)


N\left(y\right)=(1)/(e^y),\:\quad M\left(x\right)=\left(x+2\right)^2


\mathrm{Solve\:}\:(1)/(e^y)y'\:=\left(x+2\right)^2


(1)/(e^y)y'\:=x^(2)+4+4x

Integrate both the sides with respect to dx


\int(1)/(e^y)y'dx\:=\intx^(2)dx+4\int dx+4\int x dx


\int e^(-y)dy\:=\intx^(2)dx+4\int dx+4\int x dx


-(1)/(e^(y))\:=(x^(3))/(3)+4x+4(x^(2))/(2)+c_1


-(1)/(e^(y))\:=(x^(3))/(3)+4x+2x^(2)+c_1

Since, IVP is y(1)=0

put x=1 and y=0 in above equation


-(1)/(e^(0))\:=(1^(3))/(3)+4(1)+2(1)^(2)+c_1


-1\:=(1)/(3)+4+2+c_1


-1\:=(19)/(3)+c_1

add both the sides by
-(19)/(3)


-1-(19)/(3)\:=(19)/(3)-(19)/(3)+c_1


-1-(19)/(3)\:=c_1


-(22)/(3)\:=c_1

so,


-(1)/(e^(y))\:=(x^(3))/(3)+4x+2x^(2)-(22)/(3)

Multiply both the sides by '-1'


(1)/(e^(y))\:=-(x^(3))/(3)-4x-2x^(2)+(22)/(3)


e^(-y)\:=-(x^(3))/(3)-4x-2x^(2)+(22)/(3)

Take natural logarithm both the sides,


-y\:=\ln(-(x^(3))/(3)-4x-2x^(2)+(22)/(3))

Multiply both the sides by '-1'


y\:=-\ln(-(x^(3))/(3)-4x-2x^(2)+(22)/(3))

Therefore, the solution is
y\:=-\ln(-(x^(3))/(3)-4x-2x^(2)+(22)/(3))

User Pavel Kalashnikov
by
4.8k points